ЈАЗИЧНАТА ТРАДИЦИЈА И ЈАЗИЧНИТЕ ПОДНОВУВАЊА ВО ЈАЗИКОТ НА ЗАКОНИТЕ (Filološke pripombe, 2019)
The aim of this paper is to present traditional and new language characteristics in the legislative texts in Macedonian. Republic of Macedonia exists as separate formation from 1945 (The first like republic of SFRJ, then, from 1991, like independent state). In this long period, there are different social-political changes. They influence on the Macedonian language. Therefore, we try to present effects and results on the different language levels in the evolution language process.